Leptospirosis pada Pekerja Pertanian: Sebuah Tinjauan Sistematis - Muhammad Ammar Naufal; Risti Graharti; Azelia Nusadewiarti (Medula, 2026)
Leptospirosis remains a significant global public health concern, particularly in tropical and subtropical regions such as Indonesia, where it contributes substantially to morbidity and mortality among individuals of productive age and agricultural workers. This systematic review aimed to analyze the risk factors, transmission mechanisms, and prevention strategies of leptospirosis among agricultural workers. The study reviewed scientific articles published within the last ten years (2016–2026) retrieved from PubMed, Google Scholar, and ScienceDirect using keywords related to leptospirosis, risk factors, agricultural workers, and prevention. A total of ten eligible studies were selected using the PRISMA protocol and synthesized narratively to provide a comprehensive overview of risk factors, transmission mechanisms and pathophysiology, as well as current prevention strategies for leptospirosis. The findings indicate that risk factors can be categorized into occupational factors (agricultural work, contact with livestock, non-compliance with personal protective equipment use), environmental factors (flood exposure, high rainfall, poor drainage and sanitation, and high rodent density), behavioral factors (poor hygiene practices and delayed healthcare seeking), and demographic factors (male sex and productive age). Occupational and environtmental factors were identified as the most prominent determinants of leptospirosis risk. Effective prevention requires a multidimensional One Health approach integrating individual protection, environmental control, occupational health and safety programs, and strengthened national surveillance systems.